A study on the violation of children’s rights: reforming the law on child labour issues in Malaysia / Nor Azizah Abdullah and Siti Norzaidah Mokhtar. - Abdullah, Nor Azizah; Mokhtar, Siti Norzaidah (2014)
This dissertation is about the adequacy of Children and Young Persons (Employment) Act 1966 (CYPEA 1966) in terms of protecting the child who is in employment in Malaysia. While in employment, the rights of a child may be violated. In other countries such as Australia, the law was so comprehensive in protecting the rights o f a child. In the Child Employment Act 2006 of Australia, it did not only cover the work under contract but even unpaid or involuntary work. In United States, according The Fair Labor Standards Act of 1938, it introducing a 40 hour working week. In addition, the Act also established a minimum wage. In the particular field of work, it also guarantees "time-and-a-half' for overtime and this Act forbids an acts which are oppressive to child labor under age. According to the Act again, a child under 18 years old is prohibited to do certain work that is dangerous and children under the age of 16 are prohibited to work during school hours. In CYPEA 1966 of Malaysia, they only cover and regulate a child who entered into a contract of service. Therefore, a contract of service or employment is needed for this Act to apply. The Child Employment Act 2006 of Queensland, Australia provide more comprehensive laws regarding the responsibilities of an employer compared to the CYPEA 1966 regarding the employer responsibilities towards child employee. In the Fair Labor Standards Act 1938, the responsibilities of employers towards children who work in United States, also very comprehensive. In Malaysia, the CYPEA 1966 does not emphasized on the responsibilities towards child worker in a comprehensive way. In Australia, it is an offense if the employer employed a school-aged child before they have obtained parent’s consent form, it's the same in United States. Whereas, in Malaysia they do not have such thing like parent’s consent form but they have a license that only applied in order to work in the entertainment industry.